Fundamentals of lithochemistry - Yudovich Ya. E. Yakov Elevich (Saint Petersburg, Naukoemkie technologii, 2024)
Lithochemistry is a branch of sedimentary rock geochemistry. The subject of lithochemistry is the distribution of rock-forming chemical elements. Based on the development of a data bank of about 35 thousand carefully verified silicate analyses, the theoretical foundations of lithochemistry are outlined, its main empirical regularities are formulated, examples of solving actual global problems of lithochemistry are shown, practical recommendations on computer processing of analytical data are given, promising areas of further research are outlined. The book FUNDAMENTALS OF LITHOCHEMISTRY*, published in Russia in 2000 is very popular in Russia (it has a high impact factor). Unfortunately, it is still unknown to the Western reader. This book contains a huge factual material on Russia and the former USSR (136 tables and 102 figures), completely unknown to the Western reader, a new chemical classifica-tion of rocks, as well as an original method of computer pro-cessing of chemical analyses; all this is also unknown in the West. The publication of the translation of this book will make all this factual and theoretical wealth available to the Western reader. The book is necessary for specialists dealing with geochemistry and ore genesis of sedimentary rocks and their analogues.